AN INTEGRAL EQUATION APPROACH FOR 2.5-DIMENSIONAL FORWARD AND INVERSE ELECTROMAGNETIC SCATTERING - Abubakar A.; van den Berg P.M.; Habashy T.M. (My University, 2006)
We present 2.5-D forward and inverse algorithms for modelling low-frequency electromagnetic scattering problems. These algorithms are intended to be used for interpretation of large-scale electromagnetic geophysical data. The algorithms are based on an integral equation approach. To solve the forward problem, a standard conjugate gradient normal residual method is employed, while the inverse problem is solved with the so-called multiplicative regularized contrast source inversion method. Inversion results with low-frequency electromagnetic data for single- and cross-well configurations are presented. Furthermore the advantages of combining the long-offset single-well and cross-well data are discussed. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ELECTROMAGNETIC INDUCTION; INVERSE PROBLEM; NUMERICAL TECHNIQUES; PERTURBATION METHOD